Kolokasi Bahasa Berbentuk Al-Ma’thuf dan Al-Ma’thuf A’laihi: Kata Iman dan Amal Shalih dalam Al-Quran - Irhamni, Muhammad Adam Ali Fikar (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
The Qur'an is considered a miracle and is believed to contain I'jaz Bayani, a kind of linguistic and literary excellence that is present in every word, sentence, sound, verse, and letter. One way to identify I'jaz Bayani in the Qur'an is to explore the connection between the words